Feasibility on equivalence ratio measurement via OH*, CH*, and C2* chemiluminescence and study of soot emissions in co-flow non-premixed DME/C1–C2 hydrocarbon flames - Abu Saleh, Abdallah; Hughes, Kevin J.; Hargrave, Graham; Yuan, Ruoyang (Frontiers in Fuels, 2024)
The effects of DME addition to methane and ethylene fuels on combustion characteristics of heat release, soot emissions and flame temperature were investigated experimentally and numerically in a non-premixed laminar flame configuration. The flame heat release soot volume fraction were measured experimentally using CH*, OH* and C2* chemiluminescence and planar two-colour soot pyrometry, respectively. The CH*, OH* and C2* were used to locate flame heat release regions as well as to investigate the soot signal's effect on their measurements. The ratios of the chemiluminescence pairs (OH*/CH*, OH*/C2*) were studied on the feasibility to map local equivalence ratios. Numerical calculations across a full range of DME mixing ratios were performed through 1D laminar flame simulations implemented with a detailed mechanism to provide an indication on the flame structures and profiles of key species including OH*, OH, CH*, CH, CH3, C3H3, C2H2, heat release rate (HRR), and flame temperature. An existing developed soot model was used in a 2D computational study to investigate its validity to model soot for DME (oxygenated fuel)/ C2H4/ N2 flames. Parametric studies have been carried out on some key parameters in the soot model to find optimum values that can be used in future studies. Although soot radiation intensities increased at a small amount (25%vol) of DME addition in the DME/methane flames, the soot pyrometry results showed reduced soot volume fraction with increased DME mixture ratio in both DME/methane and DME/ethylene flames studied, agreeing with the key conclusion of 1D numerical results. The flame HRR decreases with increasing addition of DME to methane and ethylene flames, and correlates with the trend of OH*, CH* profiles. The 1D simulation showed a non-monotonic correlation was observed between OH*/CH* ratios and equivalence ratios, implying a limited use of OH*/CH* for the equivalence ratio measurement in non-premixed flames with DME additions.